Effect of Dyslipidaemia on Arrhythmia in Diabetic Patients (Bangladesh Medical Journal, 2017)
Dyslipidaemia is an important risk factor for cardiovascular morbidity and mortality. This cross-sectional study aims to find out the effect of dyslipidaemia on arrhythmia in diabetic patients. A total of sixty (60) diabetic patients, 31 were male and 29 were female, mean age was 59.58±11.38 (range 40 to 84) years with arrhythmia were selected at the department of Cardiology at Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorder(BIRDEM) General Hospital, Dhaka over a period of six months from January to July 2014. All the patients were accomplished with 24 hours Holter ECG monitoring, among them 40 were dyslipidaemia with mean age 60.7±13.1years and 20 were without dyslipidaemia with mean age 58±10.3 years (p-value was 0.424). Mean pulse, systolic and diastolic blood pressure were 78±15 (range 55-98) beats/min, 132±20 (range 90-180) mm of Hg and 79±8 (range 60-100) mm of Hg respectively. Mean maximum and minimum heart rate were 114±22 and 57±14 beats respectively. Mean cholesterol level was 222.58±55.51 mg/dl, mean triglyceride 241.26±98.81 mg/dl, LDL 135.53±35.61 mg/dl and HDL 41.46 ±15.46 mg/dl. Mean supraventricular beats in 24 hours was 12031± 4201 with dyslipidaemia and 8522± 2099 without dyslipidaemia which was statistically significant. Mean ventricular beats in 24 hours was 13472 ± 4872 with dyslipidaemia and 8754 ± 2689 without dyslipidaemia which was also statistically significant. Arrhythmia was found more common among diabetic patients having dyslipidaemia than without dyslipidaemia.Bangladesh Med J. 2017 Jan; 46 (1): 20-24